Altered lysosome distribution is an early neuropathological event in neurological forms of Gaucher disease. Issue 5 (28th February 2017) - Zigdon, Hila; Meshcheriakova, Anna; Farfel‐Becker, Tamar; Volpert, Giora; Sabanay, Helena; Futerman, Anthony H.
Abstract : In the lysosomal storage disorder Gaucher disease (GD), glucosylceramide (GlcCer) accumulates due to the defective activity of glucocerebrosidase. A subset of GD patients develops neuropathology. We now show mislocalization of Limp2‐positive puncta and a large reduction in the number of Lamp1‐positive puncta, which are associated with impaired tubulin. These changes occur at an early stage in animal models of GD, prior to development of overt symptoms and considerably earlier than neuronal loss. Altered lysosomal localization and cytoskeleton disruption precede the neuroinflammatory pathways, axonal dystrophy and neuronal loss previously characterized in neuronal forms of GD. Abstract :